Effect of intensity modulated radiotherapy on lymphocytes in patients with esophageal squamous cell carcinoma and its clinical significance - Tian, Xiufang; Hou, Yong; Guo, Jianping; Wu, Haiyan; Nie, Limin; Wang, Hang; Zhang, Yan; Lv, Yajuan (Frontiers in Oncology, 2023)
Background Radiotherapy usually leads to a decrease in the total number of lymphocytes in patients with esophageal cancer. The factors that causing lymphopenia and the clinical significance of lymphopenia are studied in this article. Patients and methods 110 patients with esophageal squamous cell carcinoma who had undergo intensity-modulated radiation therapy were enrolled. Statistical methods were used to analyze the correlation between lymphopenia and total survival in patients with esophageal cancer during radiotherapy, and analyze the correlations between nutritional factors and lymphopenia. Results There were 11 patients with the lowest lymphocyte value with level 1-2 during radiotherapy, accounting for 10% of all the patients, and 110 patients with level 3-4, accounting for 90% of all the patient. In all the enrolled patients, the incidence of lymphocyte nadir G1, G2, G3 and G4 MinALC during radiotherapy accounted for 0.91%, 9.09%, 62.73% and 27.27%, respectively.KM survival analysis showed that the overall survival of patients in the group (MinALC ≤ 0.41×109/L) was significantly lower than that of the patients in the other group (MinALC>0.43×109/L). Nutritional indicators were positively correlated with the decline degree of lymphocytes. The minimal value of lymphocyte can predict the occurrence of grade 3-4 radiation pneumonitis. Conclusion Lymphopenia induced by radiotherapy can predict survival and radiation pneumonitis. Nutritional factors such as hemoglobin and albumin were positively correlated with total lymphocytes numbers induced by radiotherapy.